Răspuns :
a + b + c = 112
a = b + 11
c = b + 2
b + 11 + b + b + 2 = 112
3 b + 13 = 112
3 b = 112 - 13
3 b = 99
b = 99 : 3
b = 33
a = 33 + 11
a = 44
c = 33 + 2
c = 35
proba :
44 + 33 + 35 = 112
a = b + 11
c = b + 2
b + 11 + b + b + 2 = 112
3 b + 13 = 112
3 b = 112 - 13
3 b = 99
b = 99 : 3
b = 33
a = 33 + 11
a = 44
c = 33 + 2
c = 35
proba :
44 + 33 + 35 = 112
a+b+c=112
b=a-11
c=b+2
a+b+c=112=>a+a-11+b+2=a+a-11+a-11+2=
3a-11+2=112/-2
3a-11=110/-11
3a=10/:3
Și de aici calculezi tu,a,b,c
b=a-11
c=b+2
a+b+c=112=>a+a-11+b+2=a+a-11+a-11+2=
3a-11+2=112/-2
3a-11=110/-11
3a=10/:3
Și de aici calculezi tu,a,b,c